Academic Senate Minutes 2004-10-14 - Academic Senate:::::::::
Chair's report. Correspondence. Agenda approved. Minutes of 9/30/04 approved. Course Outline Policy referred to EPC. Revised Concentration in Global Studies: Europe approved. New Concentration in Global Studies: Global Environmental Policy approved. President's report. Bill Poe and Mike Ezra approved for the Campus Planning Committee. Procedures for Faculty Trustee Nominations approved. Provost report. Vice President of Administration and Finance report. Executive Vice President of Associated Student report. Chair-Elect report. Statewide Senator report. APC report. Good of the Order.